Prof. Thomas Anthony D’Amico: looking beyond the boundary - Fan, Li-Hua (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
The AATS Focus (Focus on thoracic surgery: lung cancer and esophageal cancer) Conference 2018 was held in Guangzhou on November 3rd and 4th. More than 40 scholars from home and abroad gathered together to share the latest cutting-edge technology in thoracic surgery with the conference attendees. After the meeting, we were honored to invite Professor Thomas A. D’Amico, one of the chairmen of the meeting, to be interviewed.